Rahab : From Harlot to Heroine By God’s Grace - Suheru Suheru (STT Kingdom, 2023)
The book of Joshua introduces one of the Old Testament's most unusual and controversial heroines. Rahab, a prostitute from the city of Jericho in Canaan, known for helping the Israelites defeat the city of Jericho and for her position in the genealogy of Jesus Christ. Various questions raged regarding Rahab, stirring up the mind to pay attention to her story again. By using the method literature or literature review with a descriptive and analytical approach, is expected to be able to answer these questions. His incredible story illustrates how Allah accepts a person no matter what their background